The nonlinear correlation between the cardiometabolic index and the risk of diabetes: A retrospective Japanese cohort study - Zha, Fubing; Cao, Changchun; Hong, Mengru; Hou, Huili; Zhang, Qionghua; Tang, Bin; Hu, Haofei; Han, Yong; Zan, Yibing; Wang, Yulong; Xu, Jianwen (Frontiers in Endocrinology, 2023)
Abstract Background: The cardiometabolic index (CMI) has been proposed as a novel indicator of cardiometabolic status. However, evidence on the connection between CMI and diabetes mellitus (DM) risk was limited. The aim of our study was to examine the connection between CMI and DM risk among a large cohort of Japanese adults. Methods: This retrospective cohort study recruited 15453 Japanese adults without diabetes at baseline who underwent physical examinations at the Murakami Memorial Hospital between 2004 and 2015. Cox proportional-hazards regression was applied to evaluate the independent connection between CMI and diabetes. Our study performed a generalized smooth curve fitting (penalized spline technique) and an additive model (GAM) to determine the non-linear correlations between CMI and DM risk. In addition, a set of sensitivity analyses and subgroup analyses were employed to evaluate the connection between CMI and incident DM. Results: After controlling for confounding covariates, the CMI was found to be positively related to the DM risk in Japanese adults (HR: 1.65, 95%CI: 1.43-1.90, P<0.0001). A series of sensitivity analyses were also employed in this study to guarantee the reliability of the findings. In addition, our study discovered a non-linear correlation between CMI and diabetes risk. CMI's inflection point was 1.01. A robust positive link between CMI and diabetes incidence was also discovered to the left of the inflection point (HR: 2.96, 95%CI: 1.96-4.46, P<<0.0001). However, their association was not significant when CMI was higher than 1.01 (HR: 1.27, 95%CI: 0.98-1.64, P=0.0702). Subgroup analyses revealed that the association between CMI and DM risk was stable, and other variables did not affect the association. Conclusion: Increased CMI levels at baseline correlate to incident DM. The relationship between CMI and incident DM is also non-linear. High CMI levels are associated with an increased risk for DM when CMI is below 1.01.